Tindak Pengancaman Muka dalam Anime Sen To Chihiro No Kamikakushi Karya Hayao Miyazaki - Asmarany, Githa; Gorethy Nie Nie, Maria; Wiriani, Ni Made (Humanis, 2017)
This research is applying Politeness Theory that proposed by Brown and Levinson (1987) as the main theory and supported by the concepts about politeness in Japanese that proposed by Mizutani and Mizutani (1987). The aim of this research is to identify the utterance that count as face-threatening acts, identify politeness strategy that used in that utterance and factors influencing the choice of strategies. The result of the analysis, there are 8 kinds of utterance threaten positive face and 7 kinds of utterance threaten negative face that found in this anime. Politeness strategies used are bald on record strategy, off record strategy, positive politeness strategy and negative politeness strategy. Those politeness strategies that used are influenced by some factors there are familiarity, age, social relationship, social status, group membership and situation.